Comprehension of prescriptions and errors in taking prescribed medicines by veterans - Polypharmacy a problem underrated - Anuj Singhal; Arun Kumar Yadav; Shankar Subramanian; Basant Kumar Pathak; Aakriti Gupta; Vivek Aggarwal (Wolters Kluwer Medknow Publications, 2021)
Background: Polypharmacy is a significant problem in the elderly. The veteran population is unique in terms of better access to health-care services and higher educational qualifications. However, the studies to assess the burden and effects of polypharmacy in this cohort are rare. Hence, the research was done to find the prevalence of polypharmacy in the veteran population. Methods: In this cross-sectional observational study, we included veterans with more than 35 years visiting the medical outpatient department. All participants were interviewed about polypharmacy after taking informed consent. Results: Out of 394 patients included in the study, 110 were prescribed five or more medicines for their illnesses (27.91%: 95% confidence interval [CI] 21.1%-30%). More than 95% (377/394) of the study participants were unaware of the concept of polypharmacy. There was high compliance to treatment in veterans (97.46%, 95% CI 95.1%-98.6%). Conclusion: This study shows that the prevalence of polypharmacy is significant in veterans, including patients in their fourth and fifth decades of life, despite fewer morbidities.